Analisis Penerapan Biaya Lingkungan Dalam Kaitan Pelaporan Akuntansi Pada PLTMG 30 MW Baubau - Wahyuni, Diny; Abdullah, Muntu; Asni, Nur (Media Akuntansi Perpajakan, 2025)
This study aims to analyze the implementation of environmental cost accounting at the 30 MW Baubau Gas Engine Power Plant (PLTMG) through an assessment of five main stages: identification, recognition, measurement, presentation, and disclosure of environmental costs. This study employs a descriptive qualitative approach, encompassing primary and secondary data obtained through interviews, observations, and documentation. The results indicate that the implementation of environmental cost accounting at the 30 MW Baubau PLTMG reflects the company's commitment to sustainable environmental management. Environmental costs have been identified through a dedicated account named "Environmental and Occupational Health and Safety Costs." Although the recognition, measurement, and presentation stages have been conducted in accordance with PSAK Number 201 of 2024, disclosure in the Notes to Financial Statements remains limited and does not yet provide detailed information regarding environmental costs.